Correction: Accuracy of the Fluorescence-Activated Cell Sorting Assay for the Aquaporin-4 Antibody (AQP4-Ab): Comparison with the Commercial AQP4-Ab Assay Kit. - Jiwon Yang; Sung Min Kim; Yoo-Jin Kim; So Young Cheon; Boram Kim; Kyeong Cheon Jung; Kyung Seok Park (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0162900.].